ANALISIS PENERAPAN TOTAL PRODUCTIVE MAINTANANCE (TPM) DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) DI PT XYZ - Fatimah Sri Mulyati; Muhamad Taufik Septiadi; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
This study aims to analyze the application of Total Productive Maintenance (TPM) in a pharmaceutical company in Bandung which is currently moving from an increasingly widespread industrial location, so that there are new products. TPM is a useful system in increasing productivity, increasing productivity on various production tools and equipment with only the necessary maintenance investment. Evaluation of the implementation of the TPM pillars is carried out through the overall equipment effectiveness (OEE) analysis method, visual management, lost time injury (LTI) and time accident rate (TAR). Another result is that the implementation of the planned maintenance pillar has not reached the target according to the standard, both in terms of availability and performance rate parameters. The pillar that has not been implemented in this company is autonomous maintenance. The conclusion from this research is that PT XYZ has not effectively implemented TPM in its factory operations. The recommendation from this research is the need for the implementation of autonomous maintenance pillars and scheduled replacement of engine components to solve problems that exist in the factory and can be focused in particular on critical work areas